Matematični model zavarovalnega procesa - Bizjak-Mlakar, Julijana (Uporabna informatika (Ljubljana), 1996)
Modeling of financial and cash flow in insurance is one of the exacting tasks performed in insurance by actuaries. Variables in such models are mostly random variables. When preparing a model of claim process, acturies frequently use a simulation of compound Poisson distribution. The simulation can be very complex, when using the classical methods. It might be particularly difficult and problematic in case we want to include into the model various suppositions, simulation of costs, inflation, investment return,including dynamic control or enhancing the model to a period of many years. In the paper, instead of the classical process, we divide the insurance process intoindividual processes which are thus easier to control. Individual calculations are made by the generator of random processes. The usefulness of the model might be enlarged by including periodical nature of financial and cash flows.
Keywords: matematični model; modeliranje finančnih tokov; uporaba modela; zavarovalništvo